Unpacking the role of workers' heterogeneity in the representation and regulation of platform work. A focus of the case of the Just Eat Takeaway agreement in Italy - Francesco Bonifacio; Arianna Marcolin (Cuadernos de Relaciones Laborales, 2024)
This article examines the issue of heterogeneity in relation to workers' representation within digital platforms. Specifically, the research analyses the regulatory process that took place within the food-delivery sector in Italy, investigating how the heterogeneity of couriers is reflected in the Just Eat Takeaway agreement signed in 2021. The novel contribution of this paper is to relate two perspectives – those of workers and unions – that have rarely been considered together in the literature on digital labour platforms. Based on extensive qualitative research in Milan, the heterogeneity of riders is synthesized into a threefold typology identified by three metaphors: the explorer, the entrepreneur and the labourer. It is argued that the introduction of a standard employment contract has led to an increase in workers’ rights and social protection. However, the current form of the agreement favours less vulnerable riders – the explorer – at the expense of those who are more numerous and dependent on platform income – the entrepreneur and the labourer. We conclude that this agreement can be interpreted mainly as a means for trade unions to legitimise their institutional role in the socio-economic arena and strengthen their power resources for future negotiations.